2002
DOI: 10.1051/0004-6361:20021175
|View full text |Cite
|
Sign up to set email alerts
|

Old stellar Galactic disc in near-plane regions according to 2MASS: Scales, cut-off, flare and warp

Abstract: Abstract.We have pursued two different methods to analyze the old stellar population near the Galactic plane, using data from the 2MASS survey. The first method is based on the isolation of the red clump giant population in the color-magnitude diagrams and the inversion of its star counts to obtain directly the density distribution along the line of sight. The second method fits the parameters of a disc model to the star counts in 820 regions. Results from both independent methods are consistent with each othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
371
5
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 269 publications
(418 citation statements)
references
References 37 publications
41
371
5
1
Order By: Relevance
“…LC01 find counts for m K ≤ 9.0 of approximately 2000 using DENIS data averaged over Δ = 5 • . We can estimate the counts expected by a model, in this case using a similar model as proposed by LC01 with disk density given by López-Corredoira et al (2002, 2004, with the luminosity function proposed by Eaton et al (1984) and the counts in the Galactic bar based on the density distribution proposed by López-Corredoira et al (2007) with the luminosity function considered as an average of the disk and bulge luminosity function. We have obtained counts in good agreement with ones observed by VVV.…”
Section: Discussionmentioning
confidence: 99%
“…LC01 find counts for m K ≤ 9.0 of approximately 2000 using DENIS data averaged over Δ = 5 • . We can estimate the counts expected by a model, in this case using a similar model as proposed by LC01 with disk density given by López-Corredoira et al (2002, 2004, with the luminosity function proposed by Eaton et al (1984) and the counts in the Galactic bar based on the density distribution proposed by López-Corredoira et al (2007) with the luminosity function considered as an average of the disk and bulge luminosity function. We have obtained counts in good agreement with ones observed by VVV.…”
Section: Discussionmentioning
confidence: 99%
“…The asymmetry of the warp was long identified in HI gas (Burton 1988;Levine et al 2006;Kalberla & Dedes 2008) and even in stars (López-Corredoira et al 2002;Reylé et al 2009). But this is the first time that it is shown that the shape varies with the age of the tracers considered.…”
Section: Dependence Of the Warp Flare And Scale Length With Agementioning
confidence: 98%
“…The evidence comes from gas tracers such as HI (Henderson et al 1982;Burton & te Lintel Hekkert 1986;Burton 1988;Diplas & Savage 1991;Nakanishi & Sofue 2003;Levine et al 2006) or molecular clouds (Grabelsky et al 1987;Wouterloot et al 1990;May et al 1997). Recent analysis of the outer Galaxy either from 2MASS (López-Corredoira et al 2002;Momany et al 2006;Reylé et al 2009) or from SDSS (Hammersley & López-Corredoira 2011) has led to the conclusion that even the stars follow a warped structure. However, it has not been clearly established that the shape of the warp is similar or deviates from the gas structure.…”
Section: Introductionmentioning
confidence: 99%
“…To verify this, we made independent A V estimates using a method based on the red-clump stars as standard candles, which provides an A V -distance relation for a given position on the sky (see e.g. López-Corredoira et al 2002). We extracted stars located within 0.3 • of the pulsar position from the 2MASS All-Sky Point Source Catalogue 11 , and created a colour-magnitude diagram, K vs. J − K. We found mean J − K colours of the red-clump branch in several magnitude bins and transformed them to the A V -distance relation, as has been done by Danilenko et al (2012) for another γ-ray pulsar J1357−6429.…”
Section: The Interstellar Extinctionmentioning
confidence: 99%